ANALYSYS OF THE CORRELATION BETWEEN WHEAT DOUGH STRENGTH AND STORAGE PROTEINS - L. V. Obukhova; E. B. Budashkina (Вавиловский журнал генетики и селекции)
We analyzed the hexaploid wheat cultivars Saratovskaya 29, Novosibirskaya 67, Skala, Irtyshanka 10, and Tselinnaya 20 and their introgression lines with Triticum timofeevii Zhuk. to elucidate the correlation between dough rheological properties (dough strength) and the contents of overall protein, raw gluten, gliadin, glutenin. The ratio of glutenin and gliadin contents and their increment in the introgression lines in comparison with the parent cultivars were assessed. Dough strength was found to correlate significantly only with glutenin increase. This correlation can be utilized in breeding design.